Education and (self)formation in revisiting educational memories: an autobiographical journey from the experiences of a brazilian student (1985-1998) - Santos, José Cicero Pinto dos; Felgueiras, Margarida Louro; Ferreira, Elisabete (Debates em Educação, 2024)
This article, based on self-narrative, aims to point out the moments considered formative in my education path from the moment I arrived at an institution for poor and street kids in 1985 until the moment I finished a technical school in 1998. The use of (self)biographical narratives is defended by some authors like (Nóvoa, 1988; Josso, 1988,2007; Ferraroti, 1988; Bolívar, 2016 and Abrahão, 2003) who believe that writing/narrating the events of our personal and professional life can lead us to find meaning in our own life trajectory, and with it we can promote transformations and changes that will help us to understand ourselves and the others. This look into the past may, in some way, helps us to find and understand ourselves and think today as a person who has built a personal and professional path in living with others. The meeting with a teacher who has been dedicating her life to help socially vulnerable boys and girls was a crucial moment in the student’s educational path. The student dives into his memories and (re)visits and (re)builds moments considered formative and important for his social transformation. The meeting with a teacher was the beginning of a social and educational transformation in their lives. The theoretical and methodological foundations used for its constructions are based on the assumptions of qualitative research using (self)biographical narrative method and semi-structured interviews.